Identification of Strobilanthes crispa from Its Related Plant Using Thin-layer Chromatography Fingerprint Analysis - Hasanah, Uswatun; Irene, Angelina; Mulyati, Ade Heri; Batubara, Irmanida; Rafi, Mohamad; Rohaeti, Eti (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Strobilanthes crispa known as keji beling in Indonesia, belong to the Acanthaceae family. Thin layer chromatography (TLC) fingerprint pattern analysis is an excellent technique for evaluating and controlling the quality of raw materials containing Strobilanthes crispa. TLC fingerprints can be used to analyze the fingerprint profiles of medicinal plants for identification, authentication, and discrimination from related plants. This study aimed to develop a TLC fingerprint analysis method to identify S. crispa for quality control. Eleven bands were effectively separated using a silica gel 60 F254 TLC plate with a mobile phase of dichloromethane, ethyl acetate, and chloroform at 16:3.2:0.8. The derivatization reagent used to detect the separated bands was 10% sulfuric acid at a wavelength of 366 nm. Validation of the TLC fingerprint analysis, which evaluated the robustness, stability, specificity, and precision, met these requirements. S. crispa can be distinguished by its TLC fingerprint from sirih hutan (Piper aduncum), a related plant with similar leaf morphology. This approach could be used to identify and authenticate of S. crispa from P. aduncum.